The effect of implantation of spherical and aspherical intraocular lenses on on functional visual parameters - Kochuhur , Iryna (The Ukrainian Scientific Medical Youth Journal, 2024)
cataract is one of the main diseases that reduces visual acuity and leads to blindness, causing significant difficulties and limitations for patients in their daily lives. Every year, cataracts are getting younger and more and more people are suffering from the disease. Today, the gold standard of cataract surgery is phacoemulsification with intraocular lens (IOL) implantation. This modern and effective method of treatment requires a careful approach to the selection of intraocular lenses to maximize the result and meet the individual needs of patients. It is not only the patient's visual acuity after surgery that is important, but also the quality of their vision. The purpose of the study was to analyze and compare the effect of spherical and aspheric intraocular lens implantation on functional visual parameters (visual acuity, spherical aberrations and contrast sensitivity) in patients with age-related cataracts after surgical treatment. The study was conducted at the Department of Ophthalmology of the Bogomolets National Medical University on the basis of the Kyiv Oleksandrivska Clinical Hospital and the Medical Ophthalmology Center "Zir 100%". We analyzed 80 patients (80 eyes) aged 45 to 75 years with a diagnosis of age-related cataracts who underwent surgical intervention - phacoemulsification with IOL implantation. The patients did not have any other pathology of the visual organ or severe somatic pathology. Patients were divided into 2 groups: Group 1 - 40 patients (40 eyes) who were implanted with Alcon AcrySof Single-Piece (SA60AT) - a spherical IOL; Group 2 - 40 patients (40 eyes) who were implanted with Johnson & Johnson Tecnis Symfony - an aspherical IOL. To participate in the study, all participants had to sign an informed consent. Measurements of functional visual parameters (visual acuity, spherical aberrations and contrast sensitivity) were performed 1 day before surgery, 7 days and 1 month after surgery. According to the results obtained, visual acuity in patients after implantation of an aspheric IOL was higher than after implantation of a spherical IOL, but this difference was not statistically significant. The aspheric IOL statistically significantly reduced postoperative internal spherical aberrations by up to 50% compared to the spherical IOL and statistically significantly provided 10% higher contrast sensitivity after surgery. Thus, the implantation of an aspheric IOL gave higher contrast sensitivity in the postoperative period than the implantation of a spherical IOL. Therefore, the quality of vision in patients was higher with the implantation of an aspheric IOL.